1997
DOI: 10.1038/sj.leu.2400718
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of chromosome arm 3p in hematologic malignancies

Abstract: hematologic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 3 publications
1
23
1
1
Order By: Relevance
“…While BLAST searches did not identify a candidate disease gene for Evi27, chromosome mapping studies showed that Evi27 maps to mouse chromosome 14 in a region of human 3p21 homology . This result is interesting because treatment-related 3p21 breaks are often observed in myelodysplastic syndrome (MDS) and AML patients (Shi et al, 1996) and 3p21 is the most frequently deleted region seen in chronic myeloid leukemia (CML) (Johansson et al, 1997). Further characterization of Evi27 may therefore identify an important human disease gene.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…While BLAST searches did not identify a candidate disease gene for Evi27, chromosome mapping studies showed that Evi27 maps to mouse chromosome 14 in a region of human 3p21 homology . This result is interesting because treatment-related 3p21 breaks are often observed in myelodysplastic syndrome (MDS) and AML patients (Shi et al, 1996) and 3p21 is the most frequently deleted region seen in chronic myeloid leukemia (CML) (Johansson et al, 1997). Further characterization of Evi27 may therefore identify an important human disease gene.…”
Section: Introductionmentioning
confidence: 98%
“…EVI27 also may be a human myeloid leukemia disease gene. Recurrent treatment-related chromosome 3p21 breaks are frequently observed in myelodysplastic syndrome and acute myeloid leukemia patients (Shi et al, 1996) and 3p21 is the most frequently deleted region in human CML (Johansson et al, 1997). Future studies will be aimed at determining whether EVI27 is a human myeloid leukemia disease gene.…”
Section: Cd8mentioning
confidence: 99%
“…The patterns for clonal chromosome abnormalities in treatment-related AML seem to vary with respect to the type of cytostatic drugs used. For example, alkylating agents have been associated with total or partial losses of chromosomes 5 and 7 and deletions of the short arms of chromosomes 3 and 12, whereas topoisomerase-I1 inhibitors have been linked to structural rearrangements of chromosome bands 1 1q23 and 21q22 (8,9). In addition, in peripheral lymphocytes of healthy workers exposed to high concentrations of benzene, dose-dependent gains (mainly trisomy) of chromosome 8 (10) and deletions of chromosomes 5 and 7 (1 1) have been found.…”
mentioning
confidence: 99%
“…Overexpression of H37/Luca15/RBM5 has been demonstrated to result in cell cycle arrest and apoptosis in human lung carcinoma (22). Deletions or translocations involving 3p21 have been linked to acute leukemia, myelodysplastic syndrome and solid tumor types, including small cell lung and renal cell carcinomas (21,23,24).…”
Section: Discussionmentioning
confidence: 99%